Repeated Evolution of Chimeric Fusion Genes in the β-Globin Gene Family of Laurasiatherian Mammals - Gaudry, Michael J. (Oxford University Press, 2014)
The evolutionary fate of chimeric fusion genes may be strongly influenced by their recombinational mode of origin and the nature of functional divergence between the parental genes. In the β-globin gene family of placental mammals, the two postnatally expressed δ- and β-globin genes (HBD and HBB, respectively) have a propensity for recombinational exchange via gene conversion and unequal crossing-over. In the latter case, there are good reasons to expect differences in retention rates for the reciprocal HBB/HBD and HBD/HBB fusion genes due to thalassemia pathologies associated with the HBD/HBB “Lepore” deletion mutant in humans. Here, we report a comparative genomic analysis of the mammalian β-globin gene cluster, which revealed that chimeric HBB/HBD fusion genes originated independently in four separate lineages of laurasiatherian mammals: Eulipotyphlans (shrews, moles, and hedgehogs), carnivores, microchiropteran bats, and cetaceans. In cases where an independently derived “anti-Lepore” duplication mutant has become fixed, the parental HBD and/or HBB genes have typically been inactivated or deleted, so that the newly created HBB/HBD fusion gene is primarily responsible for synthesizing the β-type subunits of adult and fetal hemoglobin (Hb). Contrary to conventional wisdom that the HBD gene is a vestigial relict that is typically inactivated or expressed at negligible levels, we show that HBD-like genes often encode a substantial fraction (20–100%) of β-chain Hbs in laurasiatherian taxa. Our results indicate that the ascendancy or resuscitation of genes with HBD-like coding sequence requires the secondary acquisition of HBB-like promoter sequence via unequal crossing-over or interparalog gene conversion.